Highly Sensitive Voltammetric Method for Quinoline Yellow Determination on Renewable Amalgam Film Electrode - Anna Górska-Ratusznik; Dominika Różańska; Joanna Smajdor; Beata Paczosa-Bator; Robert Piech (Molecules, 2023)
A novel electrochemical method for the determination of quinoline yellow (QY) was developed using the renewable amalgam film electrode (Hg(Ag)FE). The sensors used can be characterized by good stability and long lifespan. Irreversible QY reduction peaks were recorded in 0.05 mol L−1 HCl with a potential of about −630 mV. The use of the Hg(Ag)FE electrode with a regulated working surface allowed the QY limit of detection to be as low as 0.48 nmol L−1. The obtained result is the lowest in comparison to other voltammetric methods described in the literature. The effects of parameters such as the size of the working electrode surface, influence of the pH value, accumulation time, and potential were investigated to provide precision and high sensitivity of the performed measurements. This new procedure was applied for the highly sensitive determination of quinoline yellow in different beverages, pre-workout supplements, and throat lozenges. The process of sample preparation was relatively simple. Calculated recoveries (96–107%) suggest that the method can be considered accurate.